PENERAPAN MODEL WATERFALL PADA SISTEM INFORMASI BEASISWA BERBASIS WEB - Raya, Agustina Mardeka (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
The advancement of information technology that is developing in the world of education has made the Atma Luhur campus always want to develop technology, including in offering scholarships. Scholarship information on the Atma Luhur campus is not yet known by students and prospective new students. Currently there is no computerized system to assist the registration process and scholarship management at the Atma Luhur campus. Therefore we need a web-based scholarship information system to make it easier for students to get information and register for scholarships so that every student has the right to register and get scholarships to help the student affairs department in data management. To support this scholarship system the writer uses the waterfall model in the system analyzer process. Software modeling is described by UML (Unified Manipulation Language). The result of this research is a web-based scholarship information system using the waterfall model with an object-oriented method. Software testing using the User Acceptance Test method yields 84% ​​results.